Explained infertility among the couple attending the infertility unit of Bangabandhu Sheikh Mujib Medical University (BSMMU), Bangladesh - Sultana, Arifa; Tanira, Shaorin; Adhikary, Sanchita; Keya, Kashfia Ahmed; Akhter, Sayeba (Journal of Dhaka Medical College, 2015)
Context: The causes of infertility vary from country to country among different cultural, environmental and socio economic groups. The aim of the study was to explain the causes of infertility among the couple attending infertility unit of Bangabandhu Sheikh Mujib Medical University (BSMMU), Bangladesh and to compare with previous studies of both local and abroad. Methods: This cross sectional study was carried out between September 2007 and March 2008 at infertility unit of BSMMU Hospital, Dhaka, among 110 couples, who had tried unsuccessfully for more than one year to reproduce. The data included history, physical examination and relevant investigations for female partners and male partners. Results: The age group of 25-30 years was the most vulnerable as they represented 52% of primary and 51.42% of secondary infertility. Among the 110 subfertile couples, 43.63% had female factor problems; 20% were suffering from male factor problems. In 21.81% of cases both male and female were responsible. In 14.54% cases, there were no causes, and, therefore, remain unexplained infertility. Among women, primary subfertility was 68.18%, secondary subfertility was 31.81% and among men, it was 79% and 21% respectively. Most of the infertile couples (43.64%) were trying for 2-5 years. In this study, most common cause was ovarian dysfunction (33.63%). Among them, anovulation with regular menstruation was found in 60%, polycystic ovarian disease in 32%, hyperprolactinaemia in 16% cases. Bilateral tubal occlusion was found in 8% and pelvic adhesions in 24% by doing laparoscopy. In addition, 10% of patients had endometriosis. Fibroid uterus was found in 26% cases. Among the primary subfertility cases, common causes were anovulation with regular menstruation (14.66%) and polycystic ovarian disease (12%). 40% of secondary subfertility was related with menstrual regulation (MR). Among male factors, azoospermia was found in 6.36% cases, oligozoospermia in 10.9% cases, asthenozoospermia 18.18%, teratozoospermia was in 6.36% cases. Conclusion: Primary subfertility cases were more common than secondary subfertility cases. Ovarian dysfunction was the common causes of subfertility. Other factors were abnormal semen analysis, endometriosis, tubal occlusion, pelvic adhesions and fibroid uterus. DOI: http://dx.doi.org/10.3329/jdmc.v23i1.22705 J Dhaka Medical College, Vol. 23, No.1, April, 2014, Page 114-120